Portraits of Brazil - Galvão, Walnice Nogueira (ABEI Journal, 2016)
The period of Modernism (from 1922 onwards) was also one which exhaustively attempted to understand and explain Brazil through literary works of various genres: fiction, poetry, essay. This paper attributes to these works the general category of “Portraits of Brazil”. It is important to highlight its central issue: the miscegenation of three races (indigenous peoples, white Europeans and African slaves) has formed the Brazilian population. We examine here the sources of different diagnoses and proposals.Keywords: Brazilian Modernism; Paulo Prado; Mário de Andrade; Oswaldde Andrade.